Repeated regrouping of pair-housed heifers around puberty affects their behavioural and HPA axis reactivities - Raussi, Satu; Boissy, Alain; Andanson, Stéphane; Kaihilahti, Jutta; Pradel, Philippe; Veissier, Isabelle (fr, 2006)
This paper analyses the consequences of repeated regrouping of dairy heifers according to their behaviour, stress physiology and production. Thirty-two Holstein heifers were housed in pairs. Between 11 and 13 months of age, half were subjected to 16 pen relocations each time with a new peer (regrouped heifers), while the other half remained in the same pen with the same peer (controls). The heifers were observed in standardised behavioural tests comprising sudden (opening of an umbrella), novel (an unfamiliar arena) or predator-related (dog) stimuli. All behavioural tests were conducted on three sessions between the 13th and the 16th regroupings. The functioning of the HPA axis was assessed through blockade by dexamethasone and stimulation by ACTH after the 14th regrouping and stimulation by CRF after the 15th regrouping. Weight gain was assessed during the regrouping period and reproduction (No. of inseminations before successful insemination) thereafter. Regrouped heifers reacted less than the controls to the umbrella ( = 8.23, P < 0.05). They started eating more quickly in the arena (F = 10.8, P < 0.01). In the presence of the dog, they were less active (F = 6.26, P < 0.05) and tended to look at the dog less often (F = 3.63, P < 0.10). The reduction in behavioural responses from one session to the next one was more pronounced in regrouped heifers (e.g. number of eating bouts: F (session treatment) = 4.23, P < 0.05). Regrouped heifers had lower cortisol responses to CRF. In conclusion, repeatedly regrouped heifers appear less disturbed by unusual situations and habituate to those more quickly. According to the behaviour of heifers and as suggested by their lower cortisol responses, diversity rather than stability of the social environment appears more beneficial to them.
Keywords: Ko; CRF; ACTH; lypsykarja; hiehot; eläinten käyttäytyminen; stressi; tuottavuus; heifer; cattle; domestic animals; social behaviour; regrouping; behavioural reactivity; heifer; regrouping; behavioural reactivity; social behavior; CRF-challenge; ACTH-challenge; domestic cattle; dairy-cows